A Review: Genetic Mutations in Hemoglobin: Sickle Cell Anemia - Hutham Abd Ali Abd Al Hussain; Shymaa Hamzah Daylee; Radhiah Najm Abd (Scientific Trends, 2023)
An irreversible, heritable change to the nucleotide sequence of a gene or chromosome is referred to as a mutation, or in the method through which such a shift takes place. Small-scale and large-scale mutations fall under the two groups of mutations. When one or more nucleotides are changed, removed, or added, small-scale mutations take place in the DNA. Large-scale mutations are those that arise in a specific region of a chromosome. This type of mutation has the potential to be fatal or cause significant damage, Mutations can be classified as small scale or large scale depending on their influence on the gene structure. Anemia and severe pain are symptoms of the hereditary condition sickle cell anemia. People with the illness have a defective gene that contributes to the creation of the protein hemoglobin, which carries oxygen in erythrocytes. People who carry two copies of the sickle cell gene are more likely to develop sickle cell disease. Sickle cell illness does not afflict people who have only one copy of the sickle cell gene, but their descendants may get it from them.
Keywords: Sickle cell anemia, Hemoglobin, B chain, Mutate, and heredity diseases.